Fazendo antropologia na rua: a gênese da produção social da marginalidade entre os "flanelinhas" - Prado, Francieli Muller (2016)
The large urban centers, as that marked by cultural diversity, are presented as a rich field of social research, the study provides a better understanding of the city as the context in which social relations are established. Among the various possibilities for studies in the city, the valets cars show themselves as social actors able to raise important discussions, which contribute to (de) construction of interpretations about the group and activity. The objective of this research is therefore to understand the keeper activity cars in Maringá-PR. And through the analysis of ethnographic data, demonstrate how to configure their identities, conjecture their practices and how they live invisibility and marginality. For this part is a theoretical model of Urban Anthropology, with some discussion of the city, following as it constitutes the identities of the actors in this city context and finally the empirical part of the research, which through ethnographic writing develops the description of social reality experienced by the interlocutors their daily life experiences and how the dynamics of the activity is recorded. The research is based essentially on qualitative methodological procedures, structured from three research techniques: participant observation, the photo-elicitation and Document Analysis. With the application of these techniques was possible to reveal the singularities of the group, the subjective perceptions and the social construction of the valets cars universe in Maringá streets. For, while the activity is able to integrate the subject, since the street enables the construction of many more links, it also appears as a discriminatory factor was, above all, the stigma own the car keeper activity.